Run all night [videorecording (DVD)] - Neeson, Liam; Harris, Ed, 1950-; Kinnaman, Joel, 1979- (Warner Bros. Entertainment, 2015)
Brooklyn mobster and prolific hit man Jimmy Conlon, once known as The Gravedigger, has seen better days. Longtime best friend of mob boss Shawn Maguire, Jimmy, now 55, is haunted by the sins of his past. Lately, it seems Jimmy's only solace can be found at the bottom of a whiskey glass. But when Jimmy's estranged son, Mike, becomes a target, Jimmy must make a choice between the crime family he chose and the real family he abandoned long ago.